Pengaruh Pelatihan, Profesionalisme, Kedisiplinan, Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT. PLN (Persero) UP3 Metro - Setiarini, Vika Tamara; Suryadi, Suryadi (Jurnal Manajemen DIVERSIFIKASI, 2021)
This study aims to analyze Influence of Training, Professionalism, Discipline, and The Work Environment on Employee Performance. This type of research is a quantitative study with a population of 159 employees registered at PT. PLN (Persero) UP3 Metro, only 114 samples were used in which were in accordance with predetermined criteria. The data used are secondary data distribution questionnaire in the form of a list of questions with several alternative answers for respondents. The statistical test used to test the hypothesis is the multiple linier regression analysis test and tested using the statistical package for the social science (SPSS) version 21 program. The results of statistical tests show that Influence of Training, Professionalism, Discipline, and The Work Environment on Employee Performance. Keywords : Influence of Training, Professionalism, Discipline, The Work Environment , Employee Performance.